2014
DOI: 10.1073/pnas.1320945111
|View full text |Cite
|
Sign up to set email alerts
|

CG hypomethylation in Lsh −/− mouse embryonic fibroblasts is associated with de novo H3K4me1 formation and altered cellular plasticity

Abstract: DNA methylation patterns are established in early embryogenesis and are critical for cellular differentiation. To investigate the role of CG methylation in potential enhancer formation, we assessed H3K4me1 modification in murine embryonic fibroblasts (MEFs) derived from the DNA methylation mutant Lsh −/− mice. We report here de novo formation of putative enhancer elements at CG hypomethylated sites that can be dynamically altered. We found a subset of differentially enriched H3K4me1 regions clustered at neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 42 publications
2
40
1
Order By: Relevance
“…LSH is critical for chromatin function and establishment of DNA methylation (6,7,32,39). Reports show that LSH contributes to the malignant progression of prostate cancer, melanoma, head and neck cancer, etc.…”
Section: Discussionmentioning
confidence: 99%
“…LSH is critical for chromatin function and establishment of DNA methylation (6,7,32,39). Reports show that LSH contributes to the malignant progression of prostate cancer, melanoma, head and neck cancer, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that relative transcript abundance is stable in KO MEFs (despite CG methylation loss) suggests redundancies in epigenetic silencing pathways. Interestingly, several genes that are embedded in repressed chromatin (and still silenced upon CG hypomethylation) are in part marked by de novo H3K4me1 modification in KO MEFs and belong to the neuronal lineage (Yu et al 2014). H3K4me1 can mark potential enhancers, and the lack of histone acetylation indicated that these sites are not active yet in KO MEFs but represent putative enhancers.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple pathways regulate DNA methylation, but it remains largely unknown how specific factors control methylation at a given site. Previous studies using Hells mutants examined specific genomic loci, such as immediate promoter regions or potential enhancers, and applied techniques that are biased for regions of low CG density and that have limited resolution (Xi et al 2007(Xi et al , 2009Myant et al 2011;Tao et al 2011;Yu et al 2014). In addition, fibroblast cell lines were analyzed that may have developed aberrant methylation patterns due to prolonged culture in vitro (Myant et al 2011;Tao et al 2011).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Knockout mice die perinatally with defects in lymphocyte proliferation, embryonic growth, and kidney development (Geiman et al, 2001;Geiman and Muegge, 2000). Loss leads to global DNA methylation changes including global hypomethylation at repetive sequences, as well as both hypo and hypermethylation of single copy genes (Myant et al, 2011;Tao et al, 2011b;Dunican et al, 2013;Yu et al, 2014). HELLS has been identified as a marker of mammalian stem cells with expression decreasing upon differentiation.…”
Section: Functionmentioning
confidence: 99%
“…In addition, activation of lymphocytes leads to apoptosis intead of cell proliferation (Geiman et al, 2000). Molecular studies on this mouse led to identifying HELLS as a gene necessary for DNA methylation and important for correct chromatin packaging and histone methylation (Dennis et al, 2001;Yan et al, 2003b ;Huang et al, 2004;Myant et al, 2011;Tao et al, 2011b;Yu et al, 2014).…”
Section: Note Hells Tm1kmumentioning
confidence: 99%